Modelo de simulación para la optimización de rutas de transporte para recolectores de basura en la ciudad de salcedo - Garzón Espinosa, Cristian Patricio (2019)
The purpose of this research project is to evaluate the times and distances on the transport routes for garbage collectors in the City of Salcedo (urban area), to improve their efficiency through a simulation model. In the investigation a referential of the descriptive method was made, based on the information gathering of the operation and transportation times, to later analyze these processes within the garbage collection routes and to propose an improvement proposal. The research is non-experimental and adopts a field modality, network analysis is applied by collecting data by observing and reviewing documents to perform the simulation model. The results obtained allowed to identify the operational problems in each one of the transportation routes, through the simulation aided by the Router Planner software, the optimization of the garbage collectors transport routes was determined, a solution was sought in terms of minimizing the total distance traveled during garbage collection. This work allowed to analyze the practical cases to improve the efficiency of the collection. It is concluded that the elaboration of the model allowed to optimize distances and times of the garbage collectors routes, it will be possible to reduce the travel times as well as the maintenance costs.